COMBINING VITAMIN D AND ORAL ANTIDIABETICS: EFFECTS ON GLYCATED HEMOGLOBIN A IN TYPE 2 DIABETES - Vivi Saharani Saputri; Yolanda Safitri; Tefi Nadila Putri; Azira Isnaini Salsabilla; Nabilla Syaharani; Nur Khalisha Yahya (Bajang Institute, 2026)
Background: A chronic metabolic condition known as type 2 diabetes mellitus (T2DM) develops when the body becomes less sensitive to insulin and the pancreatic β-cells are unable to adjust, resulting in elevated blood glucose concentrations. Oral antidiabetic agents (OADs) remain the mainstay of pharmacological treatment, yet many patients fail to achieve their glycemic goals. Through anti-inflammatory processes, vitamin D helps regulate gene expression, improve insulin responsiveness, and improve β-cell function. The purpose of this evidence-based case study was to assess the efficacy of OAD therapy alone against OAD therapy plus vitamin D supplementation in lowering HbA1c levels in T2DM patients. The literature search strategy was applied through PubMed, EBSCO, and the Cochrane Library using the keywords (“type 2 diabetes mellitus” AND “vitamin D” AND “glycemic control”). Eligible studies included systematic reviews or meta-analyses comparing OAD plus vitamin D with OAD alone and reporting HbA1c outcomes. Of 485 identified articles, after applying the inclusion criteria, five systematic reviews and meta-analyses qualified for analysis and were evaluated according to the CEBM appraisal criteria. Results: Four of the five included trials reported a statistically significant drop in HbA1c after using vitamin D supplements, whereas one found no impact. Overall, the findings favored vitamin D in increasing glycemic control, although the magnitude of reduction was modest. The benefit appeared greater in subjects with low vitamin D levels who underwent extended supplementation. Conclusion: Supplementing with vitamin D may help T2DM patients using OADs achieve better glycemic control. Although the reduction in HbA1c was small and not clinically significant, longer treatment duration may enhance outcomes.